2013
DOI: 10.1371/journal.pone.0080193
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Expression of Apoptosis Stimulating Protein of p53-2 (ASPP2) in Human Acute Leukemia Is Associated with Therapy Failure

Abstract: Inactivation of the p53 pathway is a universal event in human cancers and promotes tumorigenesis and resistance to chemotherapy. Inactivating p53 mutations are uncommon in non-complex karyotype leukemias, thus the p53-pathway must be inactivated by other mechanisms. The Apoptosis Stimulating Protein of p53-2 (ASPP2) is a damage-inducible p53-binding protein that enhances apoptosis at least in part through a p53-mediated pathway. We have previously shown, that ASPP2 is an independent haploinsufficient tumor sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…It reduced damaged cell death and accumulated injuries in cells, which was beneficial for tumour survival. According to our results, low ASPP2 expression independently predicted poor prognosis of ESCC patients, which is consistent with previous reports of other cancers [22,23]. The results of q RT‐PCR in this study demonstrated that the relative expression of ASPP2 mRNA was markedly downregulated in ESCC samples compared with the paired tumor adjacent tissues.…”
Section: Discussionsupporting
confidence: 92%
“…It reduced damaged cell death and accumulated injuries in cells, which was beneficial for tumour survival. According to our results, low ASPP2 expression independently predicted poor prognosis of ESCC patients, which is consistent with previous reports of other cancers [22,23]. The results of q RT‐PCR in this study demonstrated that the relative expression of ASPP2 mRNA was markedly downregulated in ESCC samples compared with the paired tumor adjacent tissues.…”
Section: Discussionsupporting
confidence: 92%
“…P53 is a central apoptotic regulator 45 , and ASPP2 is a damage-inducible p53-binding protein that enhances apoptosis through p53-dependent and p53-independent pathways 46 . Attenuation of ASPP2 is caused by hypermethylation of the promoter and 5′ UTR regions in native leukemia blasts 47 . The hypermethylation and down-regulation of ASPP2 in BmCPV infected midgut suggests that BmCPV infection may lead to hypermethylation of ASPP2, which in turn may suppress the expression of ASPP2 and facilitate the proliferation of infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…Aspp2 is lowly expressed in a variety of tumors and is related to the occurrence and development of tumors. These studies suggest that Aspp2 is a very important tumor suppressor and may be a candidate gene for gene therapy of HCC (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 91%